Performance analysis of 802.11ac with frame aggregation using NS3 - N. Khalil; A. Najid (International Journal of Electrical and Computer Engineering (IJECE), 2020)
802.11ac is an interesting standard of IEEE bringing multiple advantages than its predecessor 802.11n. 802.11ac is faster and more scalable version of 802.11n offering the capabilities of wireless Gigabit Ethernet. 802.11ac will enable access points (AP) to support more STAs with a better experience for clients and more channel bonding increasing from a maximum of 40 MHz with 802.11n up to 80 or 160 MHz with 802.11ac standard. In this paper, we analyze and evaluate the 802.11ac performance using NS3 simulator (v3.26) relying on several features like channel bonding, modulation and coding schemes, guard interval and frame aggregation. Then, we present the effect of the variation of distance between STAs and AP on the network performance in term of throughput. Finally, we capture the most relevant simulations outcomes and we indicate some research challenges for the future work.